Instilling Islamic Values on STEAM Learning in Early Childhood Education to Produce Islamic Scientist (PIAUD IAIN Kudus, 2022)
In Indonesia, most early childhood education institutions are affiliated with Muslim groups to educate future intellectuals who are clerics or knowledgeable about religion and scientists who advance science. This study aims to determine how teachers of Islamic Kindergarten/Raudhatul Athfal integrate Islamic values into STEAM instruction. The qualitative phenomenological method was employed in the research. The study enrolled 44 teachers and principals from eight Islamic Kindergartens/Raudhatul Athfal in five cities/districts throughout three provinces. The research revealed that instructors of Islamic Kindergarten/Raudhatul Athfal instill Islamic values into the STEAM curriculum by 1) integrating Islamic thematic; 2) conducting Tarbiyah Imaniyah and Islamiyah; 3) utilizing technological media, and 4) referencing the Qur'an and Hadith. The researchers concluded that implementing Islamic-based STEAM learning in Islamic Kindergarten/Raudhatul Athfal is characterized by reoccurring themes, which are subsequently translated into STEAM learning activities. The researchers urge Islamic Kindergarten/Raudhatul Athfal teachers to incorporate Islamic values throughout all STEAM curriculum components continuously.